A Hydrogen Farm Strategy for Scalable Solar Hydrogen Production with Particulate Photocatalysts. Issue 24 (31st March 2020) - Zhao, Yue; Ding, Chunmei; Zhu, Jian; Qin, Wei; Tao, Xiaoping; Fan, Fengtao; Li, Rengui; Li, Can
Abstract: Scalable solar hydrogen production by water splitting using particulate photocatalysts is promising for renewable energy utilization. However, photocatalytic overall water splitting is challenging owing to slow water oxidation kinetics, severe reverse reaction, and H2 /O2 gas separation. Herein, mimicking nature photosynthesis, a practically feasible approach named Hydrogen Farm Project (HFP) is presented, which is composed of solar energy capturing and hydrogen production subsystems integrated by a shuttle ion loop, Fe 3+ /Fe 2+ . Well‐defined BiVO4 crystals with precisely tuned 110/010 facets are ideal photocatalysts to realize the HFP, giving up to 71 % quantum efficiency for photocatalytic water oxidation and full forward reaction with nearly no reverse reaction. An overall solar‐to‐chemical efficiency over 1.9 % and a solar‐to‐hydrogen efficiency exceeding 1.8 % could be achieved. Furthermore, a scalable HFP panel for solar energy storage was demonstrated under sunlight outdoors. Abstract : The hydrogen farm project (HFP) is a feasible approach for scalable solar energy storage and hydrogen production with particulate photocatalysts mimicking photosynthesis. Bismuth vanadate crystals with precisely tuned 110/010 facets successfully realize the HFP, giving up to 71 % quantum efficiency for photocatalytic water oxidation with nearly no reverse reaction from spatial charge separation.